A forming process for a self-healing porous fibrous composite automotive thermal insulation mat
Patent Information
- Application Number
- CN202411075410.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-08-07
AI Technical Summary
[0004]植物纤维聚乳酸复合材料中,植物纤维与树脂基体的界面相容性较差,界面微观结构差,容易导致复合材料的性能下降
[0032]1.本发明首先提出易降解植物纤维物理-化学协同改性方法,能在解决纤维分散难的基础上,有效改善纤维-基体的界面结合程度,采用的化学改性剂绿色无污染,且改性后产物也不会造成环境污染。
Abstract
Description
Technical Field
[0001] This invention relates to the field of polylactic acid materials and their application technology, and in particular to a molding process for a self-healing porous fiber composite automotive heat insulation pad. Background Technology
[0002] Polylactic acid (PLA), also known as polylactide, is a polymer obtained by polymerization of lactic acid as the main raw material. Its raw materials are renewable, its production is pollution-free, and its products are biodegradable, making it an ideal green polymer material. In the automotive field, PLA can be used to produce automotive interior parts (such as automotive heat insulation pads) and non-load-bearing components, helping to reduce vehicle weight and improve fuel efficiency.
[0003] The main function of automotive heat insulation pads is to insulate the dashboard and protect the paint on the hood. They also provide sound insulation, reducing engine noise. Heat insulation pads made from polylactic acid (PLA) not only offer heat and sound insulation but also possess sterilization, biocompatibility, and environmental biodegradability properties. However, PLA has relatively low hardness and is often used in combination with various synthetic fibers, thermosetting polyurethanes, or plant fibers.
[0004] In plant fiber polylactic acid composites, the poor interfacial compatibility between plant fibers and the resin matrix, along with the poor interfacial microstructure, easily leads to a decline in the composite's performance. Traditional modification methods are inefficient and prone to environmental pollution. Summary of the Invention
[0005] The purpose of this invention is to address the shortcomings of existing technologies by proposing a physical-chemical synergistic modification method for easily degradable plant fibers. This method can effectively improve the interfacial bonding between fibers and the matrix while solving the problem of fiber dispersion. Specifically, it proposes a molding process for a self-healing porous fiber composite automotive heat insulation pad.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] A molding process for a self-healing porous fiber composite automotive heat insulation pad includes the following steps:
[0008] S1, Modification of plant fibers:
[0009] The bamboo fiber was physically modified using a cold plasma treatment method to improve the interfacial adhesion between the bamboo fiber and the polylactic acid matrix and enhance interfacial compatibility.
[0010] The bamboo fiber was chemically modified using maleic anhydride to reduce the hydroxyl content on the surface of the bamboo fiber, increase the steric hindrance of the bamboo fiber to polylactic acid, and improve the interfacial compatibility.
[0011] S2, Preparation of bamboo fiber / polylactic acid laminate:
[0012] Bamboo fibers are laid on a polylactic acid nonwoven fabric of a certain thickness according to the design requirements, which can achieve precise control of the orientation of bamboo fibers. Then, another piece of polylactic acid nonwoven fabric is used to cover the bamboo fibers, and polylactic acid is melted and penetrated into the fiber layer by hot pressing to obtain a bamboo fiber / polylactic acid laminate.
[0013] S3, Fabrication of the support layer:
[0014] Polylactic acid nonwoven fabric is impregnated in a cross-linked polyurethane casting liquid containing DA bonds with a solid content of 60%. After being removed, it is hot-pressed to obtain a polylactic acid / polyurethane composite support layer.
[0015] S4, Preparation of bamboo fiber / polylactic acid preform:
[0016] Bamboo fiber / polylactic acid layers and support layers are alternately stacked and pressed to obtain bamboo fiber / polylactic acid preform with a laminate structure.
[0017] S5, Preparation of bamboo fiber / polylactic acid foam composite material:
[0018] Bamboo fiber / polylactic acid foamed composite materials were prepared by compression molding foaming process using bamboo fiber / polylactic acid preforms.
[0019] Preferably, the cold plasma treatment method uses a jet-type atmospheric low-temperature plasma surface treatment machine, in which the obtained O2 cold plasma is sprayed onto the bamboo fiber for a treatment time of 5 seconds, a treatment distance of 10 mm, and a treatment power of 650 W.
[0020] Preferably, the chemical modification treatment includes the following steps: bamboo fiber and phenol are mixed at a weight ratio of 8:2, concentrated hydrochloric acid (HCl weight concentration of 35%) accounting for 1% of the total weight of the system is added dropwise, and soaked for 3 hours; then maleic anhydride and xylene are added, with the weight ratio of maleic anhydride, xylene and bamboo fiber being 1:3:3, and the mixture is refluxed at 140°C for 3 hours, filtered and dried to obtain maleic anhydride modified bamboo fiber.
[0021] Preferably, the thickness of the polylactic acid nonwoven fabric in S2 is 0.5-0.6 mm, and the thickness of the bamboo fiber / polylactic acid laminate is 2-2.5 mm.
[0022] Preferably, the hot pressing temperature in S2 is 200℃ and the pressure is 0.8-1MPa.
[0023] Preferably, the preparation process of the crosslinked polyurethane casting liquid containing DA bonds is as follows:
[0024] Trifunctional polyether polyol, difunctional polyether polyol and isophorone diisocyanate were mixed in a molar ratio of 1:1:4, and 0.05% by weight of dibutyltin dilaurate was added. The mixture was heated to 80°C under N2 protection and reacted for 3 hours.
[0025] The reaction system temperature was lowered to 40℃, and furfurylamine was dissolved in DMF. The molar ratio of furfurylamine to isophorone diisocyanate was 1:2. The solution was slowly added dropwise to the above reaction system. After the addition was completed, the temperature was raised to 60℃ and the reaction continued for 2 hours. The amino groups in furfurylamine reacted with the isocyanate groups to form urea carbamate bonds. At the same time, furan rings were introduced into the system to obtain a polyurethane prepolymer with furan rings.
[0026] 4,4-bismaleimide diphenylmethane was dissolved in DMF, and the molar ratio of 4,4-bismaleimide diphenylmethane and furfurylamine was 1:2. The mixture was then mixed with the above reaction system, heated to dissolve, and kept at 60°C for 24 hours to obtain a cross-linked polyurethane casting liquid containing DA bonds.
[0027] Preferably, the thickness of the polylactic acid nonwoven fabric in S3 is 1-1.1 mm, the hot pressing temperature is 180℃, the pressure is 5-6 MPa, and the thickness of the resulting polylactic acid / polyurethane composite support layer is 0.5-0.6 mm.
[0028] Preferably, the number of support layers in the bamboo fiber / polylactic acid preform is 7-10.
[0029] Preferably, the compression molding foaming process includes the following steps:
[0030] First, heat the molding foaming device to 160-170℃ and maintain a stable temperature. Then, place the dried bamboo fiber / polylactic acid preform into the mold and introduce CO2 to displace the air. Continue introducing CO2 and pressurize to 150 kg / cm³. 2 The sample is saturated under high temperature and high pressure conditions. After a period of time, CO2 gas dissolves in the polymer and reaches equilibrium. The CO2 gas in the mold cavity is released by rapid pressure relief, which causes the nucleation and growth of bubbles in the polymer, and finally the bamboo fiber / polylactic acid foamed composite material is obtained.
[0031] Compared with the prior art, the beneficial effects of the present invention are:
[0032] 1. This invention first proposes a physical-chemical synergistic modification method for easily degradable plant fibers, which can effectively improve the interfacial bonding between fibers and matrix while solving the problem of difficult fiber dispersion. The chemical modifier used is green and pollution-free, and the modified product will not cause environmental pollution.
[0033] 2. This invention uses cross-linked polyurethane containing DA bonds to fill polylactic acid nonwoven fabric, which is hot-pressed to obtain a polylactic acid / polyurethane composite support layer. This support layer is then alternately stacked with bamboo fiber / polylactic acid laminate and hot-pressed to obtain a bamboo fiber / polylactic acid preform. After foaming, a bamboo fiber / polylactic acid foamed composite material is obtained. This structure utilizes the DA-reverse DA reaction to repair the damaged bulk structure, especially effectively repairing permeable pinholes, thereby ensuring the overall waterproof, heat insulation, and sound insulation structure of the automotive heat insulation pad. Detailed Implementation
[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0035] Preparation Example 1:
[0036] The preparation process of crosslinked polyurethane casting fluid containing DA bonds is as follows:
[0037] Trifunctional polyether polyol (TMN-700), Ma=700, trifunctionality, Tianjin Xima Technology Co., Ltd.; Difunctional polyether polyol (DMN-2000), Ma=2000, difunctionality, Jiangsu Haian Petrochemical Co., Ltd.: All require vacuum drying at 120℃ for 2 hours before use; Isophorone diisocyanate (IPDI), industrial grade, Bayer AG, Germany; Furfurylamine (FAm): analytical grade, Hubei Jusheng Technology Co., Ltd.; 4,4-bismaleimide diphenylmethane (BMI), analytical grade, Hubei Jusheng Technology Co., Ltd.; Dibutyltin dilaurate (DBTL), analytical grade, Hubei Jusheng Technology Co., Ltd.; N,N-dimethylformamide (DMF), analytical grade, Hubei Jusheng Technology Co., Ltd.
[0038] Trifunctional polyether polyol, difunctional polyether polyol and isophorone diisocyanate were mixed in a molar ratio of 1:1:4, and 0.05% by weight of dibutyltin dilaurate was added. The mixture was heated to 80°C under N2 protection and reacted for 3 hours.
[0039] The reaction system temperature was lowered to 40℃, and furfurylamine was dissolved in DMF. The molar ratio of furfurylamine to isophorone diisocyanate was 1:2. The solution was slowly added dropwise to the above reaction system. After the addition was completed, the temperature was raised to 60℃ and the reaction continued for 2 hours. The amino groups in furfurylamine reacted with the isocyanate groups to form urea carbamate bonds. At the same time, furan rings were introduced into the system to obtain a polyurethane prepolymer with furan rings.
[0040] 4,4-bismaleimide diphenylmethane was dissolved in DMF, and the molar ratio of 4,4-bismaleimide diphenylmethane and furfurylamine was 1:2. The mixture was then mixed with the above reaction system, heated to dissolve, and kept at 60°C for 24 hours to obtain a cross-linked polyurethane casting liquid containing DA bonds.
[0041] Example 1:
[0042] A molding process for a self-healing porous fiber composite automotive heat insulation pad includes the following steps:
[0043] S1, Modification of plant fibers:
[0044] The bamboo fiber was physically modified using a cold plasma treatment method to improve the interfacial adhesion between the bamboo fiber and the polylactic acid matrix and enhance interfacial compatibility.
[0045] The bamboo fiber was chemically modified using maleic anhydride to reduce the hydroxyl content on the surface of the bamboo fiber, increase the steric hindrance of the bamboo fiber to polylactic acid, and improve the interfacial compatibility.
[0046] S2, Preparation of bamboo fiber / polylactic acid laminate:
[0047] Bamboo fibers are laid on a polylactic acid nonwoven fabric of a certain thickness according to the design requirements, which can achieve precise control of the orientation of bamboo fibers. Then, another piece of polylactic acid nonwoven fabric is used to cover the bamboo fibers, and polylactic acid is melted and penetrated into the fiber layer by hot pressing to obtain a bamboo fiber / polylactic acid laminate.
[0048] S3, Fabrication of the support layer:
[0049] Polylactic acid nonwoven fabric was impregnated in a cross-linked polyurethane casting liquid containing DA bonds with a solid content of 60% (Preparation Example 1). After being removed, a polylactic acid / polyurethane composite support layer was obtained by hot pressing.
[0050] S4, Preparation of bamboo fiber / polylactic acid preform:
[0051] Bamboo fiber / polylactic acid layers and support layers are alternately stacked and pressed to obtain bamboo fiber / polylactic acid preform with a laminate structure.
[0052] S5, Preparation of bamboo fiber / polylactic acid foam composite material:
[0053] Bamboo fiber / polylactic acid foamed composite materials were prepared by compression molding foaming process using bamboo fiber / polylactic acid preforms.
[0054] Among them, the cold plasma treatment method uses a jet-type atmospheric low-temperature plasma surface treatment machine. The resulting O2 cold plasma is sprayed onto the bamboo fiber for 5 seconds, 10 mm, and 650 W.
[0055] The chemical modification process includes the following steps: bamboo fiber and phenol are mixed at a weight ratio of 8:2, and concentrated hydrochloric acid (HCl weight concentration of 35%) accounting for 1% of the total weight of the system is added dropwise and soaked for 3 hours; then maleic anhydride and xylene are added, with the weight ratio of maleic anhydride, xylene and bamboo fiber being 1:3:3, and the mixture is refluxed at 140℃ for 3 hours, filtered and dried to obtain maleic anhydride modified bamboo fiber.
[0056] In S2, the thickness of the polylactic acid nonwoven fabric is 0.5-0.6 mm, and the thickness of the bamboo fiber / polylactic acid laminate is 2-2.5 mm.
[0057] In S2, the hot-pressing temperature is 200℃ and the pressure is 0.8-1MPa.
[0058] In S3, the thickness of the polylactic acid nonwoven fabric is 1-1.1 mm, the hot pressing temperature is 180℃, the pressure is 5-6 MPa, and the thickness of the resulting polylactic acid / polyurethane composite support layer is 0.5-0.6 mm.
[0059] The number of support layers in bamboo fiber / polylactic acid preforms is 7-10.
[0060] The molding foaming process includes the following steps:
[0061] First, heat the molding foaming device to 160-170℃ and maintain a stable temperature. Then, place the dried bamboo fiber / polylactic acid preform into the mold and introduce CO2 to displace the air. Continue introducing CO2 and pressurize to 150 kg / cm³. 2 The sample is subjected to high temperature and high pressure to reach saturation. After a period of time, CO2 gas dissolves in the polymer and reaches equilibrium. The CO2 gas in the mold cavity is released by rapid pressure relief, which causes the nucleation and growth of bubbles in the polymer, and finally the bamboo fiber / polylactic acid foamed composite material is obtained.
[0062] Comparative Example 1:
[0063] A molding process for a self-healing porous fiber composite automotive heat insulation pad includes the following steps:
[0064] S1, Modification of plant fibers:
[0065] The bamboo fiber was physically modified using a cold plasma treatment method to improve the interfacial adhesion between the bamboo fiber and the polylactic acid matrix and enhance interfacial compatibility.
[0066] S2, Preparation of bamboo fiber / polylactic acid laminate:
[0067] Bamboo fibers are laid on a polylactic acid nonwoven fabric of a certain thickness according to the design requirements, which can achieve precise control of the orientation of bamboo fibers. Then, another piece of polylactic acid nonwoven fabric is used to cover the bamboo fibers, and polylactic acid is melted and penetrated into the fiber layer by hot pressing to obtain a bamboo fiber / polylactic acid laminate.
[0068] S3, Fabrication of the support layer:
[0069] Polylactic acid nonwoven fabric was impregnated in a cross-linked polyurethane casting liquid containing DA bonds with a solid content of 60% (Preparation Example 1). After being removed, a polylactic acid / polyurethane composite support layer was obtained by hot pressing.
[0070] S4, Preparation of bamboo fiber / polylactic acid preform:
[0071] Bamboo fiber / polylactic acid layers and support layers are alternately stacked and pressed to obtain bamboo fiber / polylactic acid preform with a laminate structure.
[0072] S5, Preparation of bamboo fiber / polylactic acid foam composite material:
[0073] Bamboo fiber / polylactic acid foamed composite materials were prepared by compression molding foaming process using bamboo fiber / polylactic acid preforms.
[0074] Comparative Example 2:
[0075] A molding process for a self-healing porous fiber composite automotive heat insulation pad includes the following steps:
[0076] S1, Modification of plant fibers:
[0077] The bamboo fiber was chemically modified using maleic anhydride to reduce the hydroxyl content on the surface of the bamboo fiber, increase the steric hindrance of the bamboo fiber to polylactic acid, and improve the interfacial compatibility.
[0078] S2, Preparation of bamboo fiber / polylactic acid laminate:
[0079] Bamboo fibers are laid on a polylactic acid nonwoven fabric of a certain thickness according to the design requirements, which can achieve precise control of the orientation of bamboo fibers. Then, another piece of polylactic acid nonwoven fabric is used to cover the bamboo fibers, and polylactic acid is melted and penetrated into the fiber layer by hot pressing to obtain a bamboo fiber / polylactic acid laminate.
[0080] S3, Fabrication of the support layer:
[0081] Polylactic acid nonwoven fabric was impregnated in a cross-linked polyurethane casting liquid containing DA bonds with a solid content of 60% (Preparation Example 1). After being removed, a polylactic acid / polyurethane composite support layer was obtained by hot pressing.
[0082] S4, Preparation of bamboo fiber / polylactic acid preform:
[0083] Bamboo fiber / polylactic acid layers and support layers are alternately stacked and pressed to obtain bamboo fiber / polylactic acid preform with a laminate structure.
[0084] S5, Preparation of bamboo fiber / polylactic acid foam composite material:
[0085] Bamboo fiber / polylactic acid foamed composite materials were prepared by compression molding foaming process using bamboo fiber / polylactic acid preforms.
[0086] Comparative Example 3:
[0087] A molding process for a self-healing porous fiber composite automotive heat insulation pad includes the following steps:
[0088] S1, Modification of plant fibers:
[0089] The bamboo fiber was physically modified using a cold plasma treatment method to improve the interfacial adhesion between the bamboo fiber and the polylactic acid matrix and enhance interfacial compatibility.
[0090] The bamboo fiber was chemically modified using maleic anhydride to reduce the hydroxyl content on the surface of the bamboo fiber, increase the steric hindrance of the bamboo fiber to polylactic acid, and improve the interfacial compatibility.
[0091] S2, Preparation of bamboo fiber / polylactic acid laminate:
[0092] Bamboo fibers are laid on a polylactic acid nonwoven fabric of a certain thickness according to the design requirements, which can achieve precise control of the orientation of bamboo fibers. Then, another piece of polylactic acid nonwoven fabric is used to cover the bamboo fibers, and polylactic acid is melted and penetrated into the fiber layer by hot pressing to obtain a bamboo fiber / polylactic acid laminate.
[0093] S3, Fabrication of the support layer:
[0094] Polylactic acid nonwoven fabric is impregnated in a polyurethane DMF solution with a solid content of 60%, and after being removed, a polylactic acid / polyurethane composite support layer is obtained by hot pressing.
[0095] S4, Preparation of bamboo fiber / polylactic acid preform:
[0096] Bamboo fiber / polylactic acid layers and support layers are alternately stacked and pressed to obtain bamboo fiber / polylactic acid preform with a laminate structure.
[0097] S5, Preparation of bamboo fiber / polylactic acid foam composite material:
[0098] Bamboo fiber / polylactic acid foamed composite materials were prepared by compression molding foaming process using bamboo fiber / polylactic acid preforms.
[0099] The effect of bamboo fiber modification on the properties of composite materials:
[0100] The effect of Comparative Examples 1-2 and Example 1 on the properties of bamboo fiber / polylactic acid foamed composite materials was investigated. Thermal conductivity: A 20mm thick product was used for testing, according to GB / T 3399-1982 "Test Method for Thermal Conductivity of Plastics (Heat-Protected Plate Method)", with units of W / (m·K).
[0101] Tensile strength test: Performed in accordance with GB / T1040.3-2006 "Test of tensile properties of plastics", preferably using strip specimens with a width of 25mm and a length of 150mm, tensile speed of 200mm / min, and test the tensile strength (MPa) in the length direction.
[0102] The performance is shown in Table 1 below:
[0103] Table 1. Properties of bamboo fiber / polylactic acid foam composites
[0104] thermal conductivity 0.021 0.023 0.022 0.025 Tensile strength 0.82 0.76 0.73 0.79
[0105] This study demonstrates that physical modification of bamboo fiber using cold plasma treatment improves the interfacial adhesion between bamboo fiber and polylactic acid (PLA) matrix, enhancing interfacial compatibility. Chemical modification of bamboo fiber using maleic anhydride reduces the hydroxyl content on the bamboo fiber surface, increases the steric hindrance of bamboo fiber to PLA, and further improves interfacial compatibility. Improved uniformity is beneficial to the overall thermal conductivity and mechanical strength of the foamed material.
[0106] Restorative testing:
[0107] The effect of Comparative Example 3 and Example 1 on the properties of bamboo fiber / polylactic acid foam composite materials was investigated. Bamboo fiber / polylactic acid foam composite materials damaged by punctures with 10mm diameter iron nails were placed under infrared light and kept at 120°C for 1 hour, then restored to 60°C for 0.5 hours, and cooled to room temperature. The internal pores of the bamboo fiber / polylactic acid foam composite material in Example 1 were completely blocked, and the pinholes on the material surface shrank to 1-2mm. In contrast, Comparative Example 3 showed no recovery reaction, demonstrating that the polyurethane from the reverse DA reaction re-permeated into the material pores.
[0108] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A molding process for a self-healing porous fiber composite automotive heat insulation pad, characterized in that, Includes the following steps: S1, Modification of plant fibers: Bamboo fiber was physically modified using a cold plasma treatment method. Bamboo fiber was chemically modified using maleic anhydride. S2, Preparation of bamboo fiber / polylactic acid laminate: Bamboo fiber is laid on polylactic acid nonwoven fabric, and then another piece of polylactic acid nonwoven fabric is used to cover the bamboo fiber. The polylactic acid is melted and penetrated into the fiber layer by hot pressing to obtain bamboo fiber / polylactic acid laminate. S3, Fabrication of the support layer: Polylactic acid nonwoven fabric is impregnated in a cross-linked polyurethane casting liquid containing DA bonds with a solid content of 60%. After being removed, it is hot-pressed to obtain a polylactic acid / polyurethane composite support layer. S4, Preparation of bamboo fiber / polylactic acid preform: Bamboo fiber / polylactic acid layers and support layers are alternately stacked and pressed to obtain bamboo fiber / polylactic acid preform with a laminate structure. S5, Preparation of bamboo fiber / polylactic acid foam composite material: Bamboo fiber / polylactic acid foamed composite materials were prepared by compression molding foaming process using bamboo fiber / polylactic acid preforms.
2. The molding process of a self-healing porous fiber composite automotive heat insulation pad according to claim 1, characterized in that, The cold plasma treatment method uses a jet-type atmospheric low-temperature plasma surface treatment machine. The resulting O2 cold plasma is sprayed onto the bamboo fiber for 5 seconds, 10 mm, and 650 W.
3. The molding process of a self-healing porous fiber composite automotive heat insulation pad according to claim 1, characterized in that, The chemical modification treatment includes the following steps: bamboo fiber and phenol are mixed at a weight ratio of 8:2, and concentrated hydrochloric acid accounting for 1% of the total weight of the system is added dropwise. The concentrated hydrochloric acid has a weight concentration of 35%, and the mixture is soaked for 3 hours. Then, maleic anhydride and xylene are added, with a weight ratio of maleic anhydride, xylene and bamboo fiber of 1:3:
3. The mixture is refluxed at 140°C for 3 hours, filtered and dried to obtain maleic anhydride modified bamboo fiber.
4. The molding process of a self-healing porous fiber composite automotive heat insulation pad according to claim 1, characterized in that, The thickness of the polylactic acid nonwoven fabric in S2 is 0.5-0.6 mm, and the thickness of the bamboo fiber / polylactic acid laminate is 2-2.5 mm.
5. The molding process of a self-healing porous fiber composite automotive heat insulation pad according to claim 1, characterized in that, The hot-pressing temperature in S2 is 200℃, and the pressure is 0.8-1MPa.
6. The molding process of a self-healing porous fiber composite automotive heat insulation pad according to claim 1, characterized in that, The preparation process of the crosslinked polyurethane casting liquid containing DA bonds is as follows: Trifunctional polyether polyol, difunctional polyether polyol and isophorone diisocyanate were mixed in a molar ratio of 1:1:4, and 0.05% by weight of dibutyltin dilaurate was added. The mixture was heated to 80°C under N2 protection and reacted for 3 hours. The reaction system temperature was lowered to 40℃, and furfurylamine was dissolved in DMF. The molar ratio of furfurylamine to isophorone diisocyanate was 1:
2. The solution was slowly added dropwise to the above reaction system. After the addition was completed, the reaction was carried out for 1 hour, and then the temperature was raised to 60℃ and the reaction was continued for 2 hours to obtain a polyurethane prepolymer with a furan ring end. 4,4-bismaleimide diphenylmethane was dissolved in DMF, and the molar ratio of 4,4-bismaleimide diphenylmethane and furfurylamine was 1:
2. This mixture was then mixed with the above polyurethane prepolymer reaction system, heated to dissolve, and kept at 60°C for 24 hours to obtain a cross-linked polyurethane casting liquid containing DA bonds.
7. The molding process of a self-healing porous fiber composite automotive heat insulation pad according to claim 1, characterized in that, The thickness of the polylactic acid nonwoven fabric in S3 is 1-1.1 mm, the hot pressing temperature is 180℃, the pressure is 5-6 MPa, and the thickness of the resulting polylactic acid / polyurethane composite support layer is 0.5-0.6 mm.
8. The molding process of a self-healing porous fiber composite automotive heat insulation pad according to claim 1, characterized in that, The number of support layers in the bamboo fiber / polylactic acid preform is 7-10.
9. The molding process of a self-healing porous fiber composite automotive heat insulation pad according to claim 1, characterized in that, The molding foaming process includes the following steps: First, heat the molding foaming device to 160-170℃ and maintain a stable temperature. Then, place the dried bamboo fiber / polylactic acid preform into the mold and introduce CO2 to displace the air. Continue introducing CO2 and pressurize to 150 kg / cm³. 2 The sample is subjected to high temperature and high pressure to reach saturation. After a period of time, CO2 gas dissolves in the polymer and reaches equilibrium. The CO2 gas in the mold cavity is released by rapid pressure relief, which causes the nucleation and growth of bubbles in the polymer, and finally the bamboo fiber / polylactic acid foamed composite material is obtained.
Citation Information
Patent Citations
Complete biodegradable polylactic acid composite material and method for preparing same
CN101333330A
Polylactic acid material for automobile interior trim
CN105504716A